2012
DOI: 10.4137/cmped.s8208
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Dimension of Providing Palliative Care to Children and Adolescents with Cancer

Abstract: Palliative care for children and adolescents with cancer includes interventions that focus on the relief of suffering, optimization of function, and improvement of quality of life at any and all stages of disease. This care is most effectively provided by a multidisciplinary team. Nurses perform an integral role on that team by identifying symptoms, providing care coordination, and assuring clear communication. Several basic tenets appear essential to the provision of optimal palliative care. First, palliative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 67 publications
0
14
0
6
Order By: Relevance
“…They are suspicious about the care provided if they believe that professionals are poorly prepared or that the number of professionals providing care in the sector is insufficient (1) . In a study about the dimension of child nursing care in the hospital, it was found that nursing is based on procedures, that the interaction with children and family is tangential in the care process, and that despite the family sharing the care with the nursing staff, they are not included in the care perspective (21) . This situation only contributes to the gap between what is recommended and valued as part of the nursing profession and proper for nursing professionals, causing the family to not be heard during the child's hospitalization process, contributing to their distrust in the provided care.…”
Section: Discussionmentioning
confidence: 99%
“…They are suspicious about the care provided if they believe that professionals are poorly prepared or that the number of professionals providing care in the sector is insufficient (1) . In a study about the dimension of child nursing care in the hospital, it was found that nursing is based on procedures, that the interaction with children and family is tangential in the care process, and that despite the family sharing the care with the nursing staff, they are not included in the care perspective (21) . This situation only contributes to the gap between what is recommended and valued as part of the nursing profession and proper for nursing professionals, causing the family to not be heard during the child's hospitalization process, contributing to their distrust in the provided care.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, clinical staff are often uncomfortable discussing the impending death of a child, and they also lack knowledge regarding hospice and palliative care for children at an end-of-life (EOL) stage (Nuss, Hinds, & LaFond, 2005). Healthcare professionals also often disagree on treatment course (Chen, Chen, Lo, Lin, & Wang, 2008) and palliative care discussions and care are delayed until the later stages of EOL (Docherty, Thaxton, Allison, Barfield, & Tamburro, 2012;Ghoshal, Salins, Damani, Deodhar, & Muckaden, 2016). All of these factors add to the difficulty of providing optimal palliative care for paediatric patients.…”
mentioning
confidence: 99%
“…The disease that limits life has impact on interpersonal relationships of patients and families, and noticing when and how making referrals to specialized help, favors the access to additional resources in order that patients and family members are able to maintain a good quality of life at the end of life. (4,11,12) The affirmations found in the competencies were recognized as knowledge and practices of nurses in palliative care. The consensus on specific competencies in the level of total agreement, points to confidence in the palliative potential of nurses because they claim to be able to anticipate and re-spond to the palliative care needs, understand their own limitations and the need to seek help for complex actions.…”
Section: Discussionmentioning
confidence: 99%
“…They reflect the autonomy, dignity, communication and relationship between patients and health care professionals, as well as the multidisciplinary approach, quality of life, position in relation to life and death, loss and grief, and public education as central elements for the assistance in palliative care. (12)(13)(14) The majority of nurses reached consensus in the level of partial agreement regarding the general competency identified as 'observe dynamic changes in the demographics of the population'. This may indicate that information about the approach of territoriality is incipient as knowledge and practice to be shared in the multidisciplinarity.…”
Section: Discussionmentioning
confidence: 99%